WS635 Attenuates the Anesthesia/Surgery-Induced Cognitive Impairment in Mice - Lin, Jiefu; Shen, Fuyi; Lu, Jing; Liang, Feng; Zhang, Yiying; Xie, Zhongcong; Dong, Yuanlin (Frontiers in Aging Neuroscience, 2021)
Anesthesia/surgery is associated with perioperative neurocognitive disorder (PND) in patients and induces cognitive impairment in mice. Previous studies demonstrate cyclosporine A (CsA) attenuates the anesthesia/surgery-induced cognitive impairment in mice. However, CsA has immunosuppressive effects and may not be routinely used to prevent or treat post cognitive impairment in mice or PND patients. WS635 is a nonimmunosuppressive CsA analog. We, therefore, set out to determine whether WS635 could mitigate the anesthesia/surgery-induced cognitive impairment in mice. We performed abdominal surgery under 1.4% isoflurane anesthesia (anesthesia/surgery) for 2 hours in 9 month-old wild-type mice. We treated the mice with CsA (10 mg/kg) or different doses (13.2 mg/kg, 26.4 mg/kg and 52.8 mg/kg) of WS635 before and after the anesthesia/surgery. Barnes maze and fear conditioning system were employed to evaluate the cognitive function in the mice. We measured the amounts of postsynaptic density (PSD)-95, synaptophysin, and ATP in the hippocampus and cortex of the mice using western blot and ATP Colorimetric/Fluorometric Assay, respectively. We found that the treatment with 52.8 mg/kg, but not 13.2 mg/kg or 26.4 mg/kg, of WS635 attenuated the anesthesia/surgery-induced cognitive impairment in mice and the reductions in the amounts of PSD-95, synaptophysin, and ATP in the mice brain tissues. These results have established a system to study WS635 further and suggest that we perform more experiments to determine whether WS635 can ultimately be used as one of the interventions for postoperative cognitive impairment in rodents and PND in patients.